Cyclic voltammetry and electrical impedance spectroscopy of electrodes modified with PEDOT:PSS-reduced graphene oxide composite - Ramli, Nurul Izzati; Ismail, Nur Alya Batrisya; Abd. Wahab, Mohd. Firdaus; Wan Salim, Wan Wardatul Amani (Intech Open, 2018)
Cyclic voltammetry (CV) and electrical impedance spectroscopy (EIS) are electrochemical techniques to characterize reversibility of electron transfer and impedance at the electrode-solution interface, respectively. Reduced graphene oxide (rGO) and conductive polymer PEDOT:PSS are often used to enhance electron transfer at electrode surface. This chapter provides a step-by-step methodology of CV and EIS conducted on screen-printed carbon electrode (SPCE) modified with rGO-PEDOT:PSS and brief discussion on the CV and EIS results. The CV of rGO-PEDOT:PSS shows a reversible electron transfer in comparison to SPCE modified with PEDOT:PSS. For EIS, rGO-PEDOT:PSS was found to reduce the Warburg impedance, suggesting enhanced electrode conductivity. These results suggest that rGO-PEDOT:PSS is a suitable material for biosensing purpose.